Evaluation of osteoinductive and endothelial differentiation potential of Platelet‐Rich Plasma incorporated Gelatin‐Nanohydroxyapatite Fibrous Matrix. Issue 4 (29th January 2016) - J, Anjana; Kuttappan, Shruthy; Keyan, Kripa S.; Nair, Manitha B.
Abstract: In this study, platelet‐rich plasma (PRP) was incorporated into gelatin‐nanohydroxyapatite fibrous scaffold in two forms (PRP gel as coating on the scaffold [PCSC] and PRP powder within the scaffold [PCSL] and investigated for (a) growth factor release; (b) stability of scaffold at different temperature; (c) stability of scaffold before and after ETO sterilization; and (d) osteogenic and endothelial differentiation potential using mesenchymal stem cells (MSCs). PCSC demonstrated a high and burst growth factor release initially followed by a gradual reduction in its concentration, while PCSL showed a steady state release pattern for 30 days. The stability of growth factors released from PCSL was not altered either through ETO sterilization or through its storage at different temperature. PRP‐loaded scaffolds induced the differentiation of MSCs into osteogenic and endothelial lineage without providing any induction factors in the cell culture medium and the differentiation rate was significantly higher when compared to the scaffolds devoid of PRP. PCSC performed better than PCSL. In general, PRP in combination with composite fibrous scaffold could be a promising candidate for bone tissue engineering applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 771–781, 2016.